2019
DOI: 10.1021/acs.energyfuels.9b01575
|View full text |Cite
|
Sign up to set email alerts
|

Shock Tube and Kinetic Study on the Effects of CO2 on Dimethyl Ether Autoignition at High Pressures

Abstract: First-stage and overall ignition delay times of dimethyl ether (DME) were measured in a high-pressure shock tube for various mixtures containing high amounts of CO2. The data are available for DME/air mixtures diluted with 40% CO2 as well as for the mixture of DME and oxidizer containing 20.5% O2 and 79.5% CO2. As a reference, data were also collected for mixtures containing the corresponding amounts of N2. Measurements were conducted for pressures of 15, 35, and 50 bar and a range of temperatures (744–1316 K)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 63 publications
3
26
1
Order By: Relevance
“…This was already observed for n-heptane 42 and for CO 2 -diluted DME-air mixtures. 39 Mittal et al 25 report a weak dependency on oxygen mole fraction, which is not observed here, as the oxygen mole fraction varies less compared to the mixtures investigated in Ref. 25.…”
Section: Idts Of Undiluted Dme-air Mixturescontrasting
confidence: 52%
See 4 more Smart Citations
“…This was already observed for n-heptane 42 and for CO 2 -diluted DME-air mixtures. 39 Mittal et al 25 report a weak dependency on oxygen mole fraction, which is not observed here, as the oxygen mole fraction varies less compared to the mixtures investigated in Ref. 25.…”
Section: Idts Of Undiluted Dme-air Mixturescontrasting
confidence: 52%
“…43 Hence, emission at 407 nm can be associated with first-stage ignition. 39 Chemiluminescence and pressure signals are recorded by a spectrum M2i4912-exp card with a data rate of 10 M samples/s into eight channels with a resolution of 16 bit. To reduce the size of the acquired data to the necessary only, the data acquisition is triggered by a piezoelectric pressure sensor (PCB-113B03) mounted in the driven section close to the diaphragm.…”
Section: -37 For Test Time Extensionmentioning
confidence: 99%
See 3 more Smart Citations